Assisted Living Administrators' Approaches to Advance Care Planning. (February 2022) - Abken, Elise S.; Perkins, Molly M.; Bender, Alexis A.
Objectives: This project examined administrator processes, barriers, and facilitators for conducting advance care planning in assisted living. Method: Data from qualitative interviews with 27 administrators from seven diverse assisted living communities in the metropolitan Atlanta area were linked with descriptive and administrative data collected from each site and analyzed using thematic analysis. Results: Although administrators generally contended with a lack of staff training and stakeholders' reluctance to discuss advance care planning and end-of-life care, important facilitators of advance care planning in some assisted living communities included periodic follow-up discussions of residents' wishes and successfully educating consumers about the importance of planning. Three study communities whose administrators discussed planning with residents and informal caregivers during regular care plan meetings had more advance care planning documents on file. Discussion: These findings demonstrate the potential for nonmedical organizations, such as assisted living, to successfully promote advance care planning among their members.